Determination Of The Frequency Of Endocrine Infertility In Women Of Reproductive Age - Shakhnoza Anvarova (International Journal of Medical Sciences And Clinical Research, 2025)
Infertility of endocrine origin is one of the most common pathologies among women of reproductive age and leads to a decrease in the birth rate in society. The aim of the study was a retrospective analysis of the frequency and clinical features of endocrine infertility among women of reproductive age. A retrospective analysis of the incidence of endocrine infertility in 200 women of reproductive age was conducted. Retrospective analysis showed that the main endocrine pathologies, such as hyperprolactinemia, hypothyroidism, and ovulatory dysfunction of the ovaries, accounted for 77% of all cases of infertility. Infertility and a decrease in ovarian reserve (AMG 0.8 ± 0.3 ng/ml; p<0.001), especially in late reproductive age, manifested as a central pathogenetic factor.